Chapter Il memoriale italiano di Auschwitz come occasione di formazione professionale - Burzi, Andrea (Public History of Education. Teorie, esperienze, strumenti, 2022)
The italian Auschwitz memorial in Florence has been the basis for a didactic project where a fourth class in the vocational institute "Saffi" studies the exhibition for acting as a guide for visitors. There was a integration between historic and touristic content and competencies. As there was no book able to illustrate the exhibition, Luca Bravi experience was pivotal. The pandemy has interrupted the project at the step where students would have served as guides.